Control of Brown Rot Produced by Monilinia fructicola in Peaches Using a Full-Spectrum Extract of Zuccagnia punctata Cav - Di Liberto, Melina Gabriela (2023)
Brown rot of stone fruit, caused by Monilinia spp., is one of the most important diseases worldwide, causing significant production losses. Currently, the standard practices for controlling this infection consist of repetitive use of synthetic fungicides. The global tendency encourages the demand for high-quality food products harmless to health and the environment, leading to a reduction in the use of these types of substances. Zuccagnia punctata (Fabaceae) is a perennial shrub extensively used for the treatment of fungal and bacterial infections in Argentinean traditional medicine. In this study, we isolated and characterized (morphologically and molecularly) a pathogenic and virulent strain of Monilinia fructicola, which is the most hostile species of the genus. Consequently, we explored the in vitro antifungal activity of the ethanolic extract of Z. punctata against this phytopathogen. The chalcones 2′,4′-dihydroxy-3′-methoxychalcone and 2′,4′-dihydroxychalcone were isolated from the extract and evaluated against M. fructicola demonstrating that they were responsible for this activity. To promote full-spectrum extract rather than pure compounds, we performed ex-vivo assays using fresh peaches inoculated with the pathogen, and then treated by immersion in an extract solution of 250 µg/mL concentration. Treatment with Z. punctata extract did not show a statistically significant difference from commercial fungicides in the control of fruit rot. In addition, Huh7 cell cytotoxicity evaluation showed that Z. punctata extract was less cytotoxic than commercial fungicides at the assayed concentrations. Based on our research, this plant extract could potentially offer a safer alternative to commercial fungicides for treating peach brown rot.